DNA nanostructures as promising anticancer agents: a review - Murtaza Jafari (Cancer Treatment and Research Communications, 2025)
Cancer remains a major global health burden; consequently, the development of more effective and less toxic treatment options is paramount. DNA nanostructures are a promising platform for cancer therapy harnessing the unique properties of DNA. They represent an ideal platform for therapeutics, in part because they are programmable, biocompatible, and possess unique molecular architectures. Structures such as DNA origami, tetrahedra, polyhedra, and dendrimers can serve as versatile carriers for chemotherapeutic agents, gene-silencing molecules (such as siRNA and ASOs), photosensitizers, and immunomodulatory compounds. DNA nanostructures can also enhance traditional chemotherapy and new strategies, such as gene therapy, phototherapy (PDT/PTT), and immunotherapy, by delivering genetic material, photosensitizers (PDT or PTT), or immune-response activators (e.g., CpG motifs) directly to the disease site. Preclinically, DNA nanostructures have demonstrated improved drug bioavailability, significant tumor regression, and induction of a strong immune response with fewer off-target effects or toxicities than conventional therapies. This narrative review summarizes the recent advances in DNA nanostructures as anticancer agents.